Purificiation and Some Properties of Polyphenol Oxidase from Van Apple (Golden Delicious) - Demir, Halit; Hakki Yoruk, Brahim; Savran, Ali; Ekici, Kamil (Asian Journal of Chemistry, 2010)
Polyphenol oxidase was isolated from van apple, with a 4.0-fold purification of polyphenol oxidase by ammonium sulfate and DEAE cellulose being achieved. The optimum pH was 4 and for this enzyme, the optimum temperature was 50°C. Vmax and Km values were found of Lineweaver-Burk graphs. Potassium cyanide, benzoic acid, citric acid, MnCl2, NaCl, NaNO2 and CuSO4 were used as inhibitors. The enzyme activity was inhibited by benzoic acid, CuSO4 and NaCl, polyphenol oxidase activity at 10 mM, whereas NaNO2, citric acid, KCN and MnCl2 enhanced by polyphenol oxidase activity at 10 mM.